Efficient Architecture Design For Connecting and Automating of work flows and Cloud Security Control - Kumar, N.Ashok; Sagar, R Ganga (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud computing is an upcoming paradigm that offers tremendous advantages in economical aspects, such as reduced time to market, flexible computing capabilities, and limitless computing power. To use the full potential of cloud computing, data is transferred, processed and stored by external cloud providers. However, data owners are very skeptical to place their data outside their own control sphere. This paper discusses to which degree this skepticism is justified, by presenting the Cloud Computing Confidentiality Architecture. The Cloud Computing Confidentiality Architecture is a step-by-step Architecture that creates mapping from data sensitivity onto the most suitable cloud computing architecture. The concept is extended by providing a Reference Architecture which includes a complete overview of the actors and their roles and the necessary architectural components for managing and providing cloud services